Efektivitas Pembelajaran Berbasis Permainan dalam Meningkatkan Hasil Belajar Bahasa Arab - Moch Farkhan Yuangga Al Farisi; Mustamin Mustamin; Muhammad Ihsanuddin Masdar (PT. Berkah Smart Academica, 2025)
Arabic language learning at the elementary school level often faces challenges, particularly in engaging students and improving their learning outcomes. Traditional methods, which tend to be monotonous, can hinder student involvement in the learning process. Therefore, innovation in teaching methods is needed, one of which is game-based learning. This study aims to examine the effectiveness of the game-based learning method in Arabic language instruction to enhance the learning outcomes of 5th-grade students at MI Ar-Raudhah Samarinda. This research employs a quantitative approach using a Quasi-Experimental Design with a Nonequivalent Control Group Design. The research sample consisted of 48 students, comprising 24 students from Class 5A (experimental group) and 24 students from Class 5B (control group). The research instruments included tests, observations, and documentation. The data analysis techniques utilized were independent sample t-tests and N-Gain tests. The results indicate that the post-test scores of the experimental group showed an increase of 35.12 points, from a pre-test score of 51.50 to 86.62. The independent sample t-test revealed a 2-tailed Sig. Value of 0.015 < 0.050, leading to the acceptance of the alternative hypothesis (Ha) and the rejection of the null hypothesis (H0). Additionally, the N-Gain value for the experimental class was 76.9505, which concludes that the effectiveness of the game-based learning method in Arabic language instruction to improve the learning outcomes of 5th-grade students at MI Ar-Raudhah Samarinda is categorized as highly effective.